The Effect of Play and Friendship on the Development of Life Skills in Home-Schooled Students with Special Needs (Journal of Management and Educational Sciences, 2025)
The purpose of this study is to examine the effect of play and friendship relationships on the acquisition of life skills by students with special needs within the scope of home education, based on the opinions of classroom teachers. This study, which was structured according to the phenomenology design of qualitative research designs, was conducted through semi-structured interviews with 14 special education teachers working in different provinces in the spring semester of 2025. The data were analyzed using content analysis, and themes, categories, and codes were created and evaluated based on the teachers' views. According to the research findings, home education offers important opportunities for individuals with special needs in terms of both academic and life skills; in particular, it supports the retention of learning through individualized teaching opportunities. It was observed that play and gamification techniques increase students' attention, motivation, and desire to learn, while also supporting their social-emotional development. However, it was noted that limited friendships constitute a disadvantage in terms of social interaction. The study also emphasized that active family participation in the process is a determining factor in the acquisition of life skills. In conclusion, it is recommended that game-based learning, family collaboration, and structures that provide opportunities for social interaction be developed to effectively impart life skills in home education.